The Effect of Ultrasonic Impact Treatment on Surface Roughening of Commercially Pure Titanium during Tensile Test; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Kozelskaya A. I. Anna Ivanovna; Panin A. V. Alexey Viktorovich; Kazachenok M. Marina; Romanova V. Varvara; Pochivalov Yu. Yurii (2016, 2016)
Title screen